2019
DOI: 10.31557/apjcp.2019.20.5.1471
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Spectrum and Antimicrobial Resistance Pattern in Cancer Patients with Febrile Neutropenia

Abstract: Background:Bacterial bloodstream infections are one of the most common complications in cancer patients under treatment. Bacteremia in these patients is a medical crisis that needs antibiotic treatment. The aim of this study was to determine bacterial spectrum and antimicrobial resistance pattern in febrile neutropenic cancer patients.Methods:In this prospective study, 212 cancer patients with febrile neutropenia who were referred to Shahid Sadoughi hospital in Yazd from 2012 to 2015 were participated. Bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 10 publications
2
12
2
6
Order By: Relevance
“…Among the 1352 isolated causative pathogens in adult sepsis in this study, the dominant pathogens were E. coli, K. pneumoniae, and MSSA. A number of previous studies have reported E. coli to be the most frequent pathogen in patients with severe infectious diseases (Vahedian-Ardakani et al, 2019;Mehl et al, 2017;Todorovic Markovic et al, 2019). In addition, several studies have reported S. aureus as the most frequently isolated of the grampositive pathogens (Vahedian-Ardakani et al, 2019;Todorovic Markovic et al, 2019).…”
Section: Spectrum Of Causative Pathogensmentioning
confidence: 96%
See 1 more Smart Citation
“…Among the 1352 isolated causative pathogens in adult sepsis in this study, the dominant pathogens were E. coli, K. pneumoniae, and MSSA. A number of previous studies have reported E. coli to be the most frequent pathogen in patients with severe infectious diseases (Vahedian-Ardakani et al, 2019;Mehl et al, 2017;Todorovic Markovic et al, 2019). In addition, several studies have reported S. aureus as the most frequently isolated of the grampositive pathogens (Vahedian-Ardakani et al, 2019;Todorovic Markovic et al, 2019).…”
Section: Spectrum Of Causative Pathogensmentioning
confidence: 96%
“…In contrast, E. coli was associated with significantly lower mortality in the present study. One possible explanation for the high survivability is that the E. coli were generally susceptible to many common antimicrobial agents including ciprofloxacin, gentamicin, trimethoprim-sulfamethoxazole, cephalosporins, and carbapenems (Vahedian-Ardakani et al, 2019;Guerra et al, 2003;Trecarichi and Tumbarello, 2014). Therefore, based on these insights, we are now planning another study to evaluate the twoway association between causative pathogen, types of antimicrobials used, and survival.…”
Section: Mortalitymentioning
confidence: 99%
“…5 Infeksi yang berhubungan dengan demam neutropenia tidak hanya berhubungan dengan mortalitas yang tingi, tetapi juga lama perawatan yang panjang dan biaya yang besar. [6][7][8] Terlebih angka kejadian demam neutropenia yang tinggi yaitu mencapai 96% pada pasien yang mendapatkan kemoterapi agresif selama fase induksi, dengan angka respons lengkap (complete response rate) pertama (pasca induksi) sebesar 90%. 9 Untuk itu, pemberian antibiotik empirik dengan segera sangatlah penting.…”
Section: Pendahuluanunclassified
“…Selain itu, ketersediaan data yang akurat tentang organisme patogen kausatif juga penting dalam menentukan terapi empirik untuk menurunkan angka kematian dan mencapai tujuan pengobatan. 6 Surveilans bakterial merupakan prosedur yang rutin untuk setiap pasien dengan leukemia akut sebelum menjalani kemoterapi agresif. Tujuan dari pemeriksaan ini adalah untuk mendapatkan data mengenai patogen komensal yang dapat membantu menuntun klinisi (ahli hematologi) untuk memberikan terapi antimikrobial yang tepat ketika pasien mengalami demam neutropenia.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation